Philosophy of globalization - Roldán, Concha (Walter de Gruyter, 2018)
Not so long ago, it seemed the intellectual positions on globalization were clear, with advocates and opponents making their respective cases in decidedly contrasting terms. Recently, however, the fronts have shifted dramatically. The aim of this publication is to contribute philosophical depth to the debates on globalization conducted within various academic fields - principally by working out its normative dimensions. The interdisciplinary nature of this book's contributors also serves to scientifically ground the ethical-philosophical discourse on global responsibility. Though by no means exhaustive, the expansive scope of the works herein encompasses such other topics as the altering consciousness of space and time, and the phenomenon of globalization as a discourse, as an ideology and as a symbolic form.